Analysis of the Relationships between Multiple Endocrine Hormones and Return of Spontaneous Circulation (ROSC) in Cardiac Arrest Patients: Possible Association of the Serum Free T4 Level with ROSC. (30th November 2020) - Koizumi, Go; Mikura, Kentaro; Iida, Tatsuya; Kaji, Mariko; Hashizume, Mai; Murai, Norimitsu; Kigawa, Yasuyoshi; Endo, Kei; Iizaka, Toru; Saiki, Ryo; Otsuka, Fumiko; Sasaki, Jun; et al.
Abstract : Background . Endocrine hormones are closely associated with homeostasis, so it is important to clarify hormone secretion dynamics in shock. Few reports, however, have examined the dynamics of endogenous hormone secretion relative to prognosis in cardiac arrest patients. Therefore, to clarify the roles of endocrine hormones in out-of-hospital cardiac arrest (OHCA) patients, the concentrations of anterior pituitary, thyroid, and adrenocortical hormones were measured, and their associations with return of spontaneous circulation (ROSC) were examined. Methods . The subjects were OHCA patients transported to our Emergency Department. In addition to conventional clinical laboratory tests, the following were measured: serum TSH, serum free T3, serum free T4 (F-T4), plasma ACTH, serum cortisol, serum GH, serum IGF-1, plasma aldosterone concentration (PAC), and plasma renin activity. The primary endpoint was the presence or absence of ROSC, and the secondary endpoint was 24-hour survival. Results . A total of 29 patients, 17 in the ROSC group and 12 in the non-ROSC group, were studied. There were associations between ROSC and low serum potassium, high F-T4, low cortisol, and low PAC on bivariate analyses. There were associations between ROSC and serum potassium, F-T4, and GH using the step-wise method. On multiple logistic regression analysis, a relationship between ROSC and high serum F-T4 level was identified by both methods. There were also associations between 24-hour survival and both low serum potassium and elevated blood glucose levels. Conclusions . The present findings suggest a possible relationship between the serum F-T4 level and ROSC in OHCA patients. A higher serum F-T4 level might cause an increase in the β -adrenergic response in cardiomyocytes and increased responsiveness to catecholamines and was possibly associated with ROSC.